The Role of Heat Transfer Limitations in Polymer Pyrolysis at the Microscale - Richter, Franz; Rein, Guillermo (Frontiers in Mechanical Engineering, 2018)
Pyrolysis of synthetic or natural polymers is an important process in many industries such as fire safety, thermal recycling, and biomass power generation. The kinetics of pyrolysis is usually studied by thermogravimetric analysis (TGA), which is based on measuring the mass loss of a microscale sample and measuring the temperature of the surrounding fluid during controlled heating. The literature is rich in TGA measurements, which are often assumed to be governed solely by chemical kinetics. Heat and mass transfer effects, however, can occur when the sample mass is too large. Only a few studies in the literature quantify the threshold for the initial mass, above which heat transfer effects are significant. Here, we systematically analyse the role of heat transfer in TGA measurements, review existing formulations, and provide a novel threshold for the maximum sample mass. We focus on the natural polymer cellulose, a surrogate for biomass, and split the problem into heat transfer within the sample (intraparticle) and between the sample and the fluid (interparticle). Using dimensional analysis we derive two upper bound thresholds for the initial sample mass as a function of heating. One threshold is calculated based on interparticle heat transfer and depends on flow and heating conditions as well as material and fluid properties. The other is calculated based on intraparticle heat transfer and depends on heating conditions and material properties. Both thresholds were validated with measurements and previous studies from the literature. Comparing both thresholds shows that the maximum sample mass in a TGA is dictated by interparticle heat transfer and rapidly reduces with heating rate from 1.8 mg at 10 K/min to 0.15 mg at 50 K/min. These results enable the selection of appropriate sample masses and heating conditions in TGA measurements, which in turn will lead to a better understanding of polymer pyrolysis.